PERCEPATAN TRANSFORMASI DIGITAL DI DESA NAGARAWANGI, KECAMATAN RANCAKALONG SEBAGAI UPAYA PROMOSI PEMAJUAN KEBUDAYAAN DESA - Ekawati, Dian; Rachmat, Ani; Yuliawati, Susi; Tiswaya, Waway; Suryadimulya, Agus S. (Unpad Press, 2025)
We are currently in a period that is highly influenced by digital technology. This digital transformation is radically changing the industrial structure due to the spread of technologies such as artificial intelligence, big data, cloud computing, virtual reality, augmented reality and others. Among these industries, tourism is one that occupies an important position in accelerating digital transformation. This development has spread to the villages. This community service program (PPM) “Unpad Bermanfaat” aims to support the digitalization process as a means of promoting the advancement of cultural tourism in Nagarawangi Village, Rancakalong District, Sumedang Regency. Problems that arise in this process include costs, human resources and the readiness of the authorities to make it happen. By applying the ABCD method initiated by John McKnight and Jody Kretzman which focuses on assets in the field, this program conducted surveys, Focus Group Discussions (FGD), digital optimization training, and digital marketing training. The results of this activity showed increased awareness and enthusiasm of village communities and SMEs to utilize digital platforms for promoting tourism potential and local products. The main tourism potential identified is cultural tourism, particularly the Tarawangsa traditional art in Kampung Adat Cijere, which has attracted international tourists. However, digital promotion is still limited, requiring strategic digitalization that is cost-effective and optimizes existing community resources. Keywords: digital transformation; promotion; advancement; rural culture